2019
DOI: 10.1109/access.2019.2920939
|View full text |Cite
|
Sign up to set email alerts
|

Fault Diagnosis of Rotating Machinery Based on Wavelet Domain Denoising and Metric Distance

Abstract: In the monitoring process of petrochemical equipment rotating machinery, the collected large data easily lead to valuable data loss in the pre-processing process and affecting the accuracy of the fault diagnosis. This paper proposes a method for the fault diagnosis of the rotating machinery based on the wavelet-domain denoising and metric distance. The wavelet-domain denoising uses wavelet coefficients of signal and noise that have different properties on different scales and process noisy signal wavelet coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…For example, as input samples x and z belong to a same category, their within-category RBF value is expected as (11). On the other hand, if x and z belong to different categories, their between-category RBF value is expected as (12).…”
Section: Ga-based Fault Feature Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, as input samples x and z belong to a same category, their within-category RBF value is expected as (11). On the other hand, if x and z belong to different categories, their between-category RBF value is expected as (12).…”
Section: Ga-based Fault Feature Selectionmentioning
confidence: 99%
“…From (11), (12), (13) and (14), it can be concluded that a subset of fault signatures providing both large value of ( ), This means that the algorithm explores an optimal feature vector which yields the best feature space of categories to categorize by the classifier in the following stage.…”
Section: Ga-based Fault Feature Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the golden section search method is adopted to find the optimal solution f θ * (y). Substituting the iterative schemes of algorithm 2 into the second-stage optimization (10), then, a Bi-level nested sparse optimization framework is obtained and shown in algorithm 3. The mapping SureSDS shown in algorithm 2 denotes the sparse solver with SURE-based MSE estimation, and the mapping GSS is the update criterion in golden section search method.…”
Section: Optimal Feature Detection Based On Sparse Denoisermentioning
confidence: 99%
“…A primary issue in the FDI procedure is to detect feature information from noisy measurements and many advanced signal processing methods have been developed [7], such as spectrum analysis [8], time-frequency analysis [9], wavelet transform (WT) [10], spectrum kurtosis(SK) [11], adaptive mode decomposition [12], cyclostationary descriptors [13], and deep learning [14], [15], etc. In recent years, sparsity representation based fault diagnosis (SRFD) techniques have been one of the hottest topics in the signal processing society and aroused extensive interests.…”
Section: Introductionmentioning
confidence: 99%